The Impact of Population Credit Behaviour on Employment in the Informal Sector in Russian Regions - Doroshenko , Svetlana V.; Sanaeva, Olga V. (Economy of Regions, 2025)
Employment in the informal sector is a significant issue for national economies, with approximately one-fifth of Russia’s economically active population working in this sector. At the same time, household debt levels are rising in many regions, which could drive additional work, including in the informal sector. This study explores whether credit behaviour influences changes in informal sector employment across Russian regions. Using panel data from 2005 to 2021 for 83 Russian regions, the analysis draws on data from Rosstat and EMISS. The initial panel consisted of 1,411 observations. The estimation was conducted using the system GMM method. The dependent variable represents the share of people employed in the informal sector out of the total employed population aged 15-72 in each region. Key explanatory variables include total population debt and debt related to housing and mortgage loans. Control variables account for the region’s development level, economic structure, age-specific unemployment rates, family dynamics, and education institutions. The econometric analysis reveals a statistically significant negative impact of mortgage and housing debt on informal sector employment, while no effect was found for total debt. Additionally, higher levels of education and industrial production correlate with a reduction in informal sector employment. Conversely, an increase in GRP, a larger agricultural sector, higher unemployment among the elderly, and rising divorce rates contribute to higher informal sector employment. These findings can inform the development and implementation of state strategies and national projects.